Modification of Turen Bentonite with AlCl3 for Esterification of Palmitic Acid - Abdullah Abdulloh; Siti Maryam; Nanik Siti Aminah; Triyono Triyono; Wega Trisunaryanti; Mudasir Mudasir; Didik Prasetyoko Didik Prasetyoko (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
Natural Turen bentonite has been modified and applied as catalyst for palmitic acid esterification. Modification of natural Turen bentonite was conducted by cation exchange method using AlCl3 solution. Catalyst characterization was performed on X-ray Fluoroscence, X-ray Diffraction, nitrogen adsorption-desorption and infrared spectroscopy techniques. The catalytic activity test in the esterification reaction of palmitic acid with methanol was conducted by bath at 65 °C with a variation of reaction time of 1, 2, 3, 4 and 5 h. Catalytic activity has been observed qualitatively using GC-MS and quantitatively by changes in acid number. The analysis showed the formation of Al3+-bentonite. Observation on the elements has shown that the presence of calcium decreased from 10.2% to 4.17%, with an increase of aluminium content from 9.9% to 13%. Diffraction line at 2θ 5.7379º became 5.6489º, along with changes in d-spacing of 15.3895 Å to 15.6319 Å. The surface area increased from 83.78 m2/g to 91.26 m2/g, while Brönsted acid sites increased from 10.2 µmol/g to 67.5 µmol/g and Lewis acid sites increased from 94.9 µmol/g to 132 µmol/g. Furthermore, Al3+-bentonite has showed as active catalyst in the esterification reaction of palmitic acid with palmitic acid with conversion of 78.78% for 5 h. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)